A Hierarchical Evaluation of Regional Climate Simulations. (20th August 2013) - Leung, L. Ruby; Ringler, Todd; Collins, William D.; Taylor, Mark; Ashfaq, Moetasim
Abstract : Global climate models (GCMs) are the primary tools for predicting the evolution of the climate system. Through decades of development, GCMs have demonstrated useful skill in simulating climate at continental to global scales. However, large uncertainties remain in projecting climate change at regional scales, which limits the ability of scientists to help decision makers in cities and communities strategize how best to adapt to and mitigate climate change.